A Syllabus for Teaching Peritoneal Dialysis to Patients and Caregivers. Issue 6 (November 2016) - Figueiredo, Ana E.; Bernardini, Judith; Bowes, Elaine; Hiramatsu, Miki; Price, Valerie; Su, Chunyan; Walker, Rachael; Brunier, Gillian
Being aware of controversies and lack of evidence in peritoneal dialysis (PD) training, the Nursing Liaison Committee of the International Society for Peritoneal Dialysis (ISPD) has undertaken a review of PD training programs around the world in order to develop a syllabus for PD training. This syllabus has been developed to help PD nurses train patients and caregivers based on a consensus of training program reviews, utilizing current theories and principles of adult education. It is designed as a 5-day program of about 3 hours per day, but both duration and content may be adjusted based on the learner. After completion of our proposed PD training syllabus, the PD nurse will have provided education to a patient and/or caregiver such that the patient/caregiver has the required knowledge, skills and abilities to perform PD at home safely and effectively. The course may also be modified to move some topics to additional training times in the early weeks after the initial sessions. Extra time may be needed to introduce other concepts, such as the renal diet or healthy lifestyle, or to arrange meetings with other healthcare professionals. The syllabus includes a checklist for PD patient assessment and another for PD training. Further research will be needed to evaluate the effect of training using this syllabus, based on patient and nurse satisfaction as well as on infection rates and longevity of PD as a treatment.